Diabetes Mellitus-Associated Functional Hypercortisolism Impairs Sexual Function in Male Late-Onset Hypogonadism - Tirabassi, G.; Corona, G.; Lamonica, G. R.; Lenzi, A.; Maggi, M.; Balercia, G. (Hormone and Metabolic Research, 2016)
Functional hypercortisolism is generated by conditions able to chronically activate hypothalamic-pituitary-adrenal axis and has been proven to have a negative role in several complications. However, no study has evaluated the possible influence of diabetes mellitus-associated functional hypercortisolism on male hypogonadism and sexual function. We aimed to identify any association of hypothalamic-pituitary-adrenal axis dysregulation measures with testosterone and sexual function in men simultaneously affected by diabetes mellitus and late-onset hypogonadism. Fifteen diabetes mellitus and late-onset hypogonadism subjects suffering from functional hypercortisolism and fifteen diabetes mellitus and late-onset hypogonadism subjects who were free of functional hypercortisolism were retrospectively reviewed. Clinical, hormonal, and sexual parameters were considered. Hypercortisolemic subjects showed higher values of body mass index, waist, and glycated hemoglobin and lower ones of testosterone compared to normocortisolemic ones. All sexual parameters, except for orgasmic function, were significantly worse in hypercortisolemic than in normocortisolemic subjects. Hypercortisolemic patients showed higher values of cortisol after dexamethasone and urinary free cortisol as well as a lesser ACTH response after corticotropin releasing hormone test (ACTH area under curve) compared to normocortisolemic ones. No significant association was found at Poisson regression analysis between hormonal and sexual variables in normocortisolemic patients. In hypercortisolemic subjects, negative and significant associations of cortisol response after corticotropin releasing hormone (cortisol area under curve) with erectile function (β: −0.0008; p: 0.015) and total international index of erectile function score (β: −0.0006; p: 0.001) were evident. This study suggests for the first time the impairing influence of the dysregulated hypothalamic-pituitary-adrenal axis on sexual function in diabetes mellitus-associated late-onset hypogonadism.
Keywords: testosterone; international index of erectile function questionnaire; hypothalamic-pituitary-adrenal (HPA) axis